2023
DOI: 10.1002/adsc.202300063
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective (3+3) Cycloaddition of Azomethine Imines with In Situ Formed Azaoxyallyl Cations from α‐Halohydroxamate

Abstract: A diastereoselective (3 + 3) cycloaddition of azomethine imines and in situ-generated azaoxyallyl cations from α-halohydroxamate promoted by a Brønsted base has been developed. A series of pyrazolo [1,2-a][1,2,4]triazin-6-ones were accessed with up to 95% yields and diastereoselectivities greater than 20:1. The asymmetric version of this reaction was explored and moderate enantioselectivity was achieved after screening a series of cinchonine-derived chiral catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Inorganic bases such as Na 2 CO 3 , K 2 CO 3 and EtONa all produced 3 a in diminished yields (Table 1, entry 6-8). Then, a brief solvent survey demonstrated that CHCl 3 was the best, the annulation finished in 12 h and produced 3 a in 91 % yield (Table 1, entry [10][11][12][13][14][15][16][17][18]. The diastereoselectivity of the product 3 a isolated from different conditions were checked by NMR, and it was found that most of the conditions gave 3 a in excellent d. r. value of more than 20 : 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic bases such as Na 2 CO 3 , K 2 CO 3 and EtONa all produced 3 a in diminished yields (Table 1, entry 6-8). Then, a brief solvent survey demonstrated that CHCl 3 was the best, the annulation finished in 12 h and produced 3 a in 91 % yield (Table 1, entry [10][11][12][13][14][15][16][17][18]. The diastereoselectivity of the product 3 a isolated from different conditions were checked by NMR, and it was found that most of the conditions gave 3 a in excellent d. r. value of more than 20 : 1.…”
Section: Resultsmentioning
confidence: 99%
“…During the preparation of this manuscript, a similar cycloaddition reaction was reported by Peng group. [18]…”
Section: Introductionmentioning
confidence: 99%